Unikanie opodatkowania jako zagadnienie etyczno-moralne z punktu widzenia łódzkich studentów - Śmigielski, Witold (Annales. Etyka w Życiu Gospodarczym, 2010)
According to the Catholic Social Teaching, tax evasion is ethically reprehensible and people who do it commit sin. The Catholic Church based its opinion first of all on the Holy Scripture (the teaching of Jesus, St. Peter’s and St. Paul’s). Also pope John Paul II, primate of Poland Stefan cardinal Wyszyński and Joseph cardinal Höffner objected to tax frauds. The survey was conducted among the students of the University of Lodz and of the Medical University of Lodz. Its aim was to examine the students’ opinion about tax evasion. The students’ answers were grouped with regard to church attendance in order to trace if there exists a correlation between church attendance and tax morality.Statistical analysis indicated a connection between church attendance and tax morality. The highest tax morality was noticed in the group of regularly practising Catholics, a bit smaller in the non-practising or unbelieving group of people and the least tax morality was noticed among the irregularly practising group of Catholics. According to the students’ opinion, the main reason to pay taxes is for fear of financial sanction. Among other reasons the respondents listed that it is a national duty or that it is necessary to cover national expenditures. It is optimistic, however, that most of the students declared to pay the taxes fairly, if they run their own corporations in the future.